HISTORICAL AND CHRONOLOGICAL ANALYSIS OF THE MANUSCRIPTS AL-FARABI’S TREATISE “RISALA FI-S SIYASA” (Journal of Oriental Studies, 2026)
The article aims to demonstrate the significance of studying the scholarly legacy of the thinker Abu Nasr al-Farabi through the methodological framework of source studies. It is well known that the philosopher’s written heritage initially circulated throughout the world primarily in manuscript form. The scientific novelty of this research lies in the fact that, as a result of our study, nearly ten manuscript versions preserved in various world archives have been identified of the treatise Risala fi-s Siyasa (رسالة في السياسة), which was first recognized in the early twentieth century (1901) as part of Abu Nasr al-Farabi’s written corpus within the field of global Farabi studies. These manuscripts are examined as independent research objects using innovative perspectives and methods of source studies, with particular attention paid to their historical and chronological characteristics.One of the main objectives of the study is to demonstrate the importance of developing the source-studies approach within national Farabi studies. In this context, particular emphasis is placed on the necessity of training specialized scholars capable of working directly with the manuscript heritage of al-Farabi in its original form. When studying the written legacy of al-Farabi, it is essential to apply the methods and approaches of source studies in a comprehensive manner. This is due to the fact that a single treatise often exists in several manuscript copies preserved in different archival collections. These copies may differ in terms of their transmission history, preservation context, physical appearance, dating, textual content, as well as their codicological features and data. From this perspective, conducting a historical and chronological analysis of the manuscript versions of the treatise Risala fi-s Siyasa (رسالة في السياسة) significantly enhances the scholarly value of the research. As a result of the study, the scientific and methodological examination of the treatise Risala fi-s Siyasa is advanced through the application of methods such as collection, classification, description, analysis, systematization, as well as historical-chronological and codicological approaches. This makes it possible to clarify its historical-chronological, paleographic, and codicological characteristics.Keywords: Abu Nasr al-Farabi, source studies, manuscript, Risala fi-s Siyasa, al-Mawʿiẓa version, historical-chronological analysis.